PENGUKURAN KUALITAS PERANGKAT LUNAK BERDASARKAN KOMPLEKSITAS MENGGUNAKAN METODE FUNCTION POINT - Fathoni - (Universitas Sriwijaya, 2009)
Before 1969, there was a crisis related to software development conducted. The crisis occurred because most of developed software was likely to produce a new problem rather than giving benefit to its user. In fact, the developed software didn’t meet with what user need. Moreover, the management and developer had difficulties to measure software quality during software development process. Metode Function Point can be used to solve this problem. It has a set of capability to list important information to predict what resource should be provided. This prediction gives a basic thing for Software Company to prepare their proposal or project plan. As well, the method could prevent or, at least, reduce a risk of managerial mistake due to underestimate in project cost planningKey words: Quality, Software, Funtion Point